Metabolic Acidosis Alters Expression of Slc22 Transporters in Mouse Kidney - Janine Gottier Nwafor; Marta Nowik; Naohiko Anzai; Hitoshi Endou; Carsten A. Wagner (Karger Publishers, 2020)
Introduction: The kidneys play a central role in eliminating metabolic waste products and drugs through transporter-mediated excretion along the proximal tubule. This task is mostly achieved through a variety of transporters from the solute carrier family 22 (SLC22) family of organic cation and anion transporters. Metabolic acidosis modulates metabolic and renal functions and also affects the clearance of metabolites and drugs from the body. We had previously shown that induction of metabolic acidosis in mice alters a large set of transcripts, among them also many transporters including transporters from the Slc22 family. Objective: Here we further investigated the impact of acidosis on Slc22 family members. Methods: Metabolic acidosis was induced for 2 or 7 days with NH4Cl, some animals also received the uricase inhibitor oxonic acid for comparison. Expression of transporters was studied by qPCR and immunoblotting. Results: NH4Cl induced no significant changes in plasma or urine uric acid levels but caused downregulation of Slc22a1 (Oct1), Slc22a6 (Oat1), Slc22a19 (Oat5), and Slc22a12 (Urat1) at mRNA level. In contrast, Slc22a4 mRNA (Octn1) was upregulated. On protein level, NH4Cl increased Octn1 (after 7 days) and Urat1 (after 2 days) abundance and decreased Oat1 (after 2 days) and Urat1 (after 7 days). Oxonic acid had no impact on protein abundance of any of the transporters tested. Conclusion: In summary, metabolic acidosis alters expression of several transporters involved in renal excretion of metabolic waste products and drugs. This may have implications for drug kinetics and clearance of waste metabolites.